EFFECT OF CRYPTOTANSHINONE ON APOPTOSIS OF LIVER CANCER CELLS AND ITS MECHANISM OF ACTION - ZHANG Haixia, LI Kangkang, CHENG Mingyang, CHEN Xuehong (精准医学杂志, 2023)
Objective To investigate the effect of cryptotanshinone (CPT) on the apoptosis of HepG2 cells and the underlying mechanism. Methods The MTT assay was used to measure the effects of CPT at final concentrations of 0, 1, 5, 10, 20, 40, and 100 μmol/L on the viability of HepG2 cells. The median lethal concentration (IC50) of CPT for HepG2 cells was calculated. HepG2 cells were divided into groups A to D for 48 h culture with CPT at final concentrations of 0, 1, 5, and 10 μmol/L, respectively. The migration ability, mitochondrial membrane potential, and apoptosis rate of HepG2 cells were determined by wound healing assay, JC-1 staining, and flow cytometry, respectively. HepG2 cells were divided into groups E to H for culture with 0 μmol/L CPT+20 μmol/L Spautin-1, 1 μmol/L CPT+20 μmol/L Spautin-1, 5 μmol/L CPT+20 μmol/L Spautin-1, 10 μmol/L CPT+20 μmol/L Spautin-1, respectively. After 48 h culture, cell viability in groups E to H was measured by the MTT assay; LC3B-Ⅱ protein expression in groups A, D, and H was determined by Western blot; the mitochondrial membrane potential in groups A, D, E, and H was measured with JC-1 staining; and cell apoptosis in groups A, D, E, and H was measured by flow cytometry. Results With the increase of CPT concentrations, the viability of HepG2 cells was decreased significantly, with the IC50 value being 3.9 μmol/L after 48 h culture. As CPT concentrations increased, the migration ability of HepG2 cells was decreased significantly (t=5.96-29.63,P<0.05); the green/red fluorescence ratio was increased significantly (t=4.24-23.36,P<0.05); the apoptosis rate of HepG2 cells was increased significantly (t=7.30-18.15,P<0.05). There was a significant difference in cell viability between groups A to H (F=231.15,P<0.05), with higher cell viability in groups E-H than in groups A-D (t=3.96-18.80,P<0.05). Group H showed significantly lower expression of the autophagy-related protein LC3B-Ⅱ than group D (t=3.51,P<0.05). The JC-1 staining results showed that groups E and H significantly differed from group D in the green/red fluorescence ratio (t=3.58,14.76,P<0.05). The results of apoptosis by flow cytometry showed significant differences between group E and group D as well as between group H and group D (t=12.38,4.99,P<0.05). Conclusion CPT can effectively inhi-bit the viability of HepG2 cells through autophagy-mediated apoptosis.